Flavones and flavanones as achetylcholinesterase inhibitors: the structure-activity relationship and molecular docking studies - Chi, Huynh Thi Kim; Nguyen, Hoang-Phuc; Dung, Hoàng Thị Kim (Vietnam Journal of Science and Technology, 2021)
Discovering and developing drugs to treat Alzheimer's disease (AD) have been a crucial target for many decades. According to a large number of later studies, acetylcholinesterase (AChE) plays an important role in AD treatment. On the other hand, flavonoids are natural compounds that possessed a wide variety of bioactivities, including the inhibitory activity on AChE. In this study, we reported the structure and activity relationship of flavone and flavanone derivatives that semi-synthesized and synthesized from flower buds of Styphnolobium japonicum (Leguminosae) and citrus peels against AChE. The results showed that the introducing of the new functional groups that leads to increasing 3-folds better AChE inhibition of compound Q2 and Q4 than that of the original. The molecular docking study was investigated in order to illuminate the experimental results and find their binding modes.